Transforming Nursing Education Through ChatGPT and Generative AI: A Systematic Review of Learning Opportunities, Educational Challenges, and Learning Outcomes - Muhamad Amirul Rasyid; Martono Martono; Nina Indriyawati; Pradita Ayu Fernanda; Chinh Nguyen Duc (Jendela Nursing Journal (JNJ), 2026)
ABSTRACT Background: The integration of generative artificial intelligence (AI), specifically ChatGPT, is driving a major transformation in nursing education to support flexible and personalized learning. However, this widespread adoption has sparked academic debate regarding institutional integrity, the risk of misinformation, and student autonomy. Purpose: This systematic review aims to identify, evaluate, and synthesize global scientific evidence regarding the opportunities, educational challenges, and student learning outcomes associated with the use of ChatGPT and generative AI in nursing education. Methods: A systematic literature review was conducted strictly following PRISMA guidelines. A comprehensive electronic search was conducted in PubMed, Scopus, ScienceDirect, and Google Scholar for English-language scholarly articles (2020–2026). Methodological quality and risk of bias were independently assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Tools. Results: Ten studies met the eligibility criteria. This review identified significant learning opportunities, including increased learning efficiency, rapid access to clinical data, optimized student engagement, and flexible support for simulation-based reflection and self-directed learning. Regarding learning outcomes, AI integration positively contributes to clinical reasoning and interactive problem-solving. However, prominent educational challenges include threats to academic integrity, plagiarism, data privacy breaches, student dependency, and the risk of misinformation. Conclusion: ChatGPT and generative AI serve as valuable complementary pedagogical tools to support clinical decision-making when properly regulated. Nursing institutions should proactively establish clear operational policies and a structured AI literacy framework to maximize the technology's opportunities while maintaining academic integrity. Keywords: ChatGPT, Generative AI, Nursing Education, Learning Opportunities, Educational.